1965
DOI: 10.1111/j.1469-7998.1965.tb01873.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of the egg shells of the Sphenisciformes

Abstract: Studies on the egg shells of a selection of Sphenisciformes, similar to previous ones on ratites and the Anatidae, have been carried out. The true shells, after removing the membrane and cover, were analysed for insoluble and soluble nitrogen, and studies were also made using histological and plastic embedding techniques. The combined studies indicate that, in addition to the large crystals running through the shell, there is often a thin layer of fine vertically orientated crystals above these. Then resting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
2

Year Published

1968
1968
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 11 publications
2
20
2
Order By: Relevance
“…A pore provides direct connection between the outside environment and the spaces between the cones. Tyler (1964bTyler ( , 1965Tyler ( , 1966bTyler ( , 1969 and Tyler & Simkiss (1959b) have studied pore structure in different types of birds by the technique of making casts (Tyler 1956) and shown that different bird groups have pore channels of different shape and structure.…”
Section: Poresmentioning
confidence: 99%
“…A pore provides direct connection between the outside environment and the spaces between the cones. Tyler (1964bTyler ( , 1965Tyler ( , 1966bTyler ( , 1969 and Tyler & Simkiss (1959b) have studied pore structure in different types of birds by the technique of making casts (Tyler 1956) and shown that different bird groups have pore channels of different shape and structure.…”
Section: Poresmentioning
confidence: 99%
“…In the same paper, Nathusius suggested that the Sphenisciformes are close to the Pelecaniformes, but this C . T Y L E R is not true since Tyler (1965) has shown structures in the Sphenisciformes which do not appear in the Pelecaniformes at present being studied.…”
Section: Shell Structure: Cuticle and Covermentioning
confidence: 85%
“…Underneath the cover the true shell is pure white. Small pimples, like those seen on Sphenisciformes egg shells (Tyler, 1965), or flatter blisters are observed on some eggs, in others the outer surface of the cover is scratched or the cover has been partly torn off. In shells where the cover was thick, it has often cracked giving a crazy paving effect.…”
Section: General Structurementioning
confidence: 94%
See 1 more Smart Citation
“…In the lab all eggshells were soaked and boiled in distilled water to remove the membranes more easily (Tyler 1965). We selected ten shell fragments from each egg at random and measured their thickness with electronic calipers to the nearest 0.01 mm.…”
Section: Methodsmentioning
confidence: 99%